2020
DOI: 10.1093/braincomms/fcaa022
|View full text |Cite
|
Sign up to set email alerts
|

Increased glutamate transporter-associated anion currents cause glial apoptosis in episodic ataxia 6

Abstract: Episodic ataxia type 6 is an inherited neurological condition characterized by combined ataxia and epilepsy. A severe form of this disease with episodes combining ataxia, epilepsy and hemiplegia was recently associated with a proline to arginine substitution at position 290 of the excitatory amino acid transporter 1 in a heterozygous patient. The excitatory amino acid transporter 1 is the predominant glial glutamate transporter in the cerebellum. However, this glutamate transporter also functions as an anion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 84 publications
(115 reference statements)
3
44
0
Order By: Relevance
“…Coupling the transport of one glutamate to several ions permits glutamate uptake against up to 10 6 -fold concentration gradients and contributes to maintaining low extracellular glutamate concentrations in the central nervous system (3,5). EAATs are not only secondary active transporters but also Cl − channels (1,2,6,7), and changes in Cl − channel function are responsible for movement disorder and epilepsy in certain forms of episodic ataxia (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Coupling the transport of one glutamate to several ions permits glutamate uptake against up to 10 6 -fold concentration gradients and contributes to maintaining low extracellular glutamate concentrations in the central nervous system (3,5). EAATs are not only secondary active transporters but also Cl − channels (1,2,6,7), and changes in Cl − channel function are responsible for movement disorder and epilepsy in certain forms of episodic ataxia (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…EAATs function as both secondary‐active glutamate transporters and anion channels (Fahlke, Kortzak, & Machtens, 2016), and we demonstrated that the P290R substitution impairs glutamate transport, but causes gain‐of‐function of EAAT1 anion channels (Hotzy, Schneider, Kovermann, & Fahlke, 2013; Winter, Kovermann, & Fahlke, 2012). To understand how increased EAAT1 anion currents cause ataxia in EA6 we generated a transgenic mouse model—the Slc1a3 P290R/+ mouse—and demonstrated that excessive chloride efflux in the second postnatal week results in Bergmann glia apoptosis and cerebellar atrophy (Kovermann et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Progression of the transport cycle results in closure of the anion channel (23), and efficient glutamate transport is only possible at the cost of low anion channel open probability. Functional analysis of SLC1A3 mutations associated with episodic ataxia type 6 revealed that excessive EAAT anion currents might perturb brain development and function (10)(11)(12)(13). The interdependency between glutamate transport and anion channel activity together with the pathological consequences of increased EAAT anion channel activity demonstrate the evolutionary need for a strict regulation of anion channel gating.…”
Section: Discussionmentioning
confidence: 99%
“…EAAT anion channels regulate neuronal excitability and synaptic transmission (7,8) as well as intracellular [Cl -]int in glial cells (9). The importance of EAAT anion channels for normal cell function is emphasized by naturally occurring mutations that cause episodic ataxia and epilepsy and alter EAAT anion currents (10)(11)(12)(13).…”
mentioning
confidence: 99%